INNV-47. TREATMENT ALLOCATION AMONG PATIENTS EVALUATED IN A MULTIDISCIPLINARY RADIATION ONCOLOGY AND NEUROSURGERY CENTRAL NERVOUS SYSTEM CLINIC. (5th November 2018) - McClelland, Shearwood; Mitin, Timur; Jaboin, Jerry; Ciporen, Jeremy
Abstract: INTRODUCTION: Treatment allocation for central nervous system disease has rarely been examined in a collaborative fashion. We describe our experience with RADIANS (RADIation oncology And NeuroSurgery), a novel multidisciplinary clinic model featuring radiation oncology in tandem with neurosurgery in a community hospital setting. METHODS: RADIANS patients were assessed to determine treatment allocation: surgery alone, radiation therapy (RT) alone, surgery with RT, or observation. Patient satisfaction was assessed via survey questionnaire. RESULTS: Forty-two patients have been seen since RADIANS inception. Median age was 65; median patient distance from RADIANS was 42.7 miles (mean=62.6; range 0.7–285); half of patients travelled more than 50 miles to receive care. Patients were most commonly treated with surgery and RT (33.3%), followed by RT alone (28.6%), observation (26.2%), and least commonly surgery alone (11.9%). More than three-fourths of patients were seen for metastatic disease of the brain and/or spine; 75% of patients delineated to RT received stereotactic body RT (SBRT). Lesions were nearly equally distributed between the brain (22 patients) and spine (20 patients). A majority of survey responders felt comfortable receiving two separate bills rather than a single bill for their RADIANS visit; all responders would recommend RADIANS for a friend/relative with a newly diagnosed spine or brain tumor. The average overall satisfaction on a 0 (not satisfied) to 5 (very satisfied) scale was 4.8. CONCLUSIONS: The RADIANS clinic model has proved viable in a community setting; half of patients travel a great distance to receive care. The most common treatment modality has involved SBRT with or without surgery. A large majority of patients are referred with metastatic disease. Thorough study will be needed to optimally evaluate the long-term impact of RADIANS on patient education and quality of care.